Collaborative Strategic Reading for Students With Learning Disabilities in Upper Elementary Classrooms. (July 2016) - Boardman, Alison G.; Vaughn, Sharon; Buckley, Pamela; Reutebuch, Colleen; Roberts, Greg; Klingner, Janette
Sixty fourth- and fifth-grade general education teachers were randomly assigned to teach Collaborative Strategic Reading (CSR; Klingner, Vaughn, Boardman, & Swanson, 2012), a set of reading comprehension strategies, or to a business-as-usual comparison group. Results demonstrate that students with learning disabilities (LD) who received CSR instruction in their general education classrooms—approximately 2 times each week over a 14-week period—made significantly greater gains in reading comprehension than students with LD in comparison classrooms ( g = .52). Teachers in CSR classrooms were also more likely to provide feedback to students and to use collaborative grouping structures.